2019
DOI: 10.1101/lm.049510.119
|View full text |Cite
|
Sign up to set email alerts
|

Reversal learning in Drosophila larvae

Abstract: Adjusting behavior to changed environmental contingencies is critical for survival, and reversal learning provides an experimental handle on such cognitive flexibility. Here, we investigate reversal learning in larval Drosophila. Using odor-taste associations, we establish olfactory reversal learning in the appetitive and the aversive domain, using either fructose as a reward or high-concentration sodium chloride as a punishment, respectively. Reversal learning is demonstrated both in differential and in absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…An important aspect of reinforcement learning theories is the idea that modulatory neurons compare predicted and actual US (to compute so-called prediction errors) and drive memory formation or extinction depending on the sign of the prediction error. While Drosophila modulatory neurons have not yet been directly shown to represent prediction errors, adult and larval Drosophila are capable of extinction 3 ; 30 ; 31 , and our study reveals candidate motifs that could support the comparison of expected and actual US. We found that modulatory neurons receive convergent input from feedback pathways from MBONs and from US pathways ( Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…An important aspect of reinforcement learning theories is the idea that modulatory neurons compare predicted and actual US (to compute so-called prediction errors) and drive memory formation or extinction depending on the sign of the prediction error. While Drosophila modulatory neurons have not yet been directly shown to represent prediction errors, adult and larval Drosophila are capable of extinction 3 ; 30 ; 31 , and our study reveals candidate motifs that could support the comparison of expected and actual US. We found that modulatory neurons receive convergent input from feedback pathways from MBONs and from US pathways ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…We assessed the contributions of different feedback pathways by repeating the optimization procedure for networks lacking such feedback and comparing their performance. Tasks included first-order conditioning and extinction which have been demonstrated in both larval 15 ; 30 and adult Drosophila 3 ; 31 , and second-order and context-dependent conditioning which have so far been investigated only in adult 32 ; 33 . In second-order conditioning, a reinforcement predicting conditioned stimulus is used to reinforce a second stimulus, while in context-dependent conditioning, the US valence depends on a previous contextual input.…”
Section: Resultsmentioning
confidence: 99%
“…Future research will include richer behavioral situations ( e.g . [ 42 , 72 , 73 ]), in vivo recording of whole-brain activity [ 23 , 24 , 25 ], modelling approaches ( e.g. [ 8 , 11 , 16 , 18 , 52 ]).…”
Section: Discussionmentioning
confidence: 99%
“…While Drosophila modulatory neurons have not yet been directly shown to represent prediction errors, adult and larval Drosophila are capable of extinction 5, 13,53,141,154 , and our study reveals candidate motifs that could support the comparison of expected and actual US. We found that modulatory neurons receive convergent input from feedback pathways from MBONs and from US pathways ( Fig.…”
Section: Convergence Of Feedback and Us Pathways Could Allow The Compmentioning
confidence: 77%